Prudent Use of Tylosin for Treatment of Mycoplasma gallisepticum Based on Its Clinical Breakpoint and Lung Microbiota Shift - Huang, Anxiong; Wang, Shuge; Guo, Jinli; Gu, Yufeng; Li, Jun; Huang, Lingli; Wang, Xu; Tao, Yanfei; Liu, Zhenli; Yuan, Zonghui; Hao, Haihong (Frontiers in Microbiology, 2021)
The aim of this study was to prudent use of tylosin for treatment chronic respiratory infectious diseases in chickens caused by Mycoplasma gallisepticum (MG) based on its clinical breakpoint (CBP) and its effect on lung microbiota. The CBP was established based on wild-type/epidemiological cutoff value (COWT/ECV), Pharmacokinetics-pharmacodynamics (PK-PD) cutoff value (COPD) and clinical cutoff value (COCL) of tylosin against MG. The minimum inhibitory concentration (MIC) of tylosin against 111 MG isolates was analyzed and the ECV was 2 μg/mL. M17 with MIC of 2 μg/mL was selected as a representative strain for PK-PD study. The COPD of tylosin against MG was 1 μg/mL. The dosage regimen formulated by PK-PD study was 3 days administration of tylosin at dose of 45.88 mg/kg b.w. with 24 hours interval. Five different MIC MGs were selected for clinical trial, and the COCL of tylosin against MG was 0.5 μg/mL. According to the CLSI decision tree, the CBP of tylosin against MG was set up as 2 μg/mL. The effect of tylosin on lung microbiota of MG infected chickens was analyzed by 16S rRNA gene sequencing. Significant change of the lung microbiota was observed in the infection group and treatment group based on the principle coordinate analysis and the venn diagrams of the core and unique OTU. The phyla of Firmicutes and Proteobacteria showed difference after MG infection and treatment. This study established the CBP of tylosin against MG. It also provided scientific data for prudent use of tylosin based on the evaluation of MG infection and tylosin treatment on the lung microbiota.